Study Kelayakan Bisnis Pendirian Fun Day Care Centre di Lippo Village, Tangerang-Banten - Silalahi, Rudy Vernando; Panjaitan, Andry Manodotua; Hermawan, Ryan (Journal Industrial Servicess, 2015)
Education is an important thing. Beside formal education in schools, parents also play role in shaping the character and mindset of their children. In fact the guidance of parents is hard to fulfill because of busyness, so it is necessary for the existence of an institution that could reflect parental figures. In Lippo Village there are housing, universities, schools, and offices therefore day care business prospects in Lippo Village is estimated quite well. This feasibility study of Fun Day day care centre is focused on six aspects, market aspects, marketing aspects, technical aspects, management aspects, legal aspects, and financial aspects. In market aspect, Fun Day potential market are workers and residents in Lippo Village that supported by the results of the questionnaire obtained. In marketing aspects, market segmentation, targeting, and positioning were carried out and marketing mix strategy was planned. Technically, Fun Day will be established in Ruko Asia Millenium Lippo Village and supported by learning material adapted to the development and achievement of children by age. The number of nannies and teacher adjusted by the ratio that have been set by the Government, discussed in the management aspect. The business legally complies with the requirement in accordance with the Law and other applicable regulation. In financial aspects both of optimistic and pessimistic calculation say Fun Day is feasible and the capital needed is Rp. 370.935.046,25. NPV Rp.55.945.713,26 with 15,91% IRR, and 49 months of payback period, the value of MARR is 12,15%. Based on the results of a study from the six aspects, it is confirmed this business is feasible.Â